CEO Compensation and Firm Performance: The Moderator Effects of Gender - Gao, Yuqing (2022)
Abstract From the last century to the present, many scholars have been interested in the relationship between CEO compensation and firm performance. They study it from different levels and perspectives, such as company type, special market, industry or country, and have obtained many theoretical and empirical discoveries. While many findings have proven that CEO compensation would influence firm performance, the intervening system controlling this influence haven’t got enough largely unexplored. The purpose of this paper is attempting to unveil the secret of ”black box” between the relationship between CEO compensation and firm performance using the agency theory and empirically test the moderating effect of gender on this association.